2023
DOI: 10.1038/s41598-022-23931-1
|View full text |Cite
|
Sign up to set email alerts
|

Time restricted feeding is associated with poor performance in specific cognitive domains of Suburb-Dwelling older Chinese

Abstract: The purpose of this study was to investigate the association between time restricted feeding (TRF) and different areas of cognitive function in the elderly in Chinese communities. This study consisted of 1353 community-dwelling Chinese older adults aged 60 years and older in Chongming area, Shanghai (563 males; the mean age, 73.38 ± 6.16 years). Mild cognitive impairment (MCI) and six different cognitive domains was assessed by the Chinese-version of Mini Mental State Examination (MMSE). Recording the eating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…The analysis also pointed out that older age, hypertension, and stroke were positively associated with participation in the TRE group. Moreover, the results indicated that TRE was negatively related to the Mini-Mental State Examination (MMSE) score (P < 0.001) in addition to the specific cognitive functions mentioned earlier ( Li et al, 2023 ).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The analysis also pointed out that older age, hypertension, and stroke were positively associated with participation in the TRE group. Moreover, the results indicated that TRE was negatively related to the Mini-Mental State Examination (MMSE) score (P < 0.001) in addition to the specific cognitive functions mentioned earlier ( Li et al, 2023 ).…”
Section: Resultsmentioning
confidence: 89%
“… Physically active individuals showed improvement in executive function, attention, inhibition, associative memory, and recognition memory during Ramadan, while sedentary individuals experienced a decline in associative learning performance. Li et al (2023) , China N = 1353, Mean age: 73.38 ± 6.16 years, 563 men and 790 women Cross-sectional study 10-h TRE vs. less than 10 h TRE Chinese-version of Mini Mental State Examination TRE was associated with a higher prevalence of cognitive impairment in the domains of orientation to place and attention/calculation. Hussin et al (2013) , Malaysia N = 31 men, Mean age: 59.7, SD: 6.3 Randomized controlled trial (RCT) Calorie-restricted dietary regime with intermittent fasting during a 3-month period The Beck Depression Inventory-II and Geriatric Depression Scale-15 were measured at baseline, as well as at weeks 6 and 12 of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, IF in males >50 years of age showed increased weight loss compared to females, suggesting that gender and age differences are important to consider while assessing IF [26]. A study conducted by Li et al [27] found that older individuals (>70 years old) with pre-existing MCIs showed worsening orientation to place and attention after IF. as a result, caution is necessary for older adults with pre-existing cognitive impairments.…”
Section: Future Directionsmentioning
confidence: 99%
“…The results were completely divergent. While the TRF strategy produced favourable results in the Italian population, studies conducted in China have even indicated a higher incidence of progression of cognitive impairment (Currenti et al, 2021;Li et al, 2023).…”
Section: Limitations Of the Research Presentedmentioning
confidence: 99%